Peningkatan Kemahiran Menulis Arab Melalui Penerapan Pembelajaran Baca Tulis Al-Qur’an - Evi Zulianah; Nicky Estu Putu Muchtar; Aridlah Sendy Robikhah (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
This article aims to describe the application of Al-Qur'an Reading and Writing Learning for Class X Students of MAN 1 Lamongan. This research uses a qualitative approach and the type of research is a case study. The data needed in this study are primary data that must be carried out through interviews and observations, as well as secondary data such as profile documents, drafts of BTQ learning programs, photos of teaching and learning activities for MAN 1 Lamongan students, and other documentation that can support the validity of research results. this and can be accounted for. The outputs in this study are the Sinta 4 Journal, ISBN Books, and HKI Written Papers. The Arabic writing skills of the tenth graders of MAN 1 Lamongan before using the BTQ book were very low. Meanwhile, Arabic writing skills after applying BTQ therapy books are getting better and better. The supporting factors are the high motivation of students, the habit of listening to murottal, and more abilities for students who graduate from Madrasah Ibtidaidah, Madrasah Tsanawiyah, and Islamic Boarding Schools. The inhibiting factors are: Physical condition that is tired due to the demands of school assignments, Class Conditions, Teacher Conditions, and Student Inactivity. To perfect the solution that has been applied, the teacher should refresh or prepare an interesting method before learning to read and write the Qur'an.